THE ADOPTION OF CONTINUOUS ONLINE AUDIT BY INTERNAL AUDITOR OF STATE UNIVERSITY IN INDONESIA A LITERATURE REVIEW - Adrianto, Zaldy (Jurnal Ekonomi dan Bisnis Terapan, 2018)
The rapid ongoing advancement in information system and technology (IT) has resulted with the steadily plummeting cost in IT service acquisition bundled with the more flexible options in infrastructure operation. Among the effected changes is the growing awareness and shifts toward continuous audit in companies in Indonesia.This research therefore aims at finding how Internal Auditor perceive the ease of use usefulness, and intention to adopt the Continuous Audit by Internal Auditor. It looks at whether there is substantial relationship observable for perceived ease of use and Intention of use of CA.This qualitative research by literature review conducted. The technique used in this research is coding the scientific articles regarding continuous audit and write the conclusion based on the main idea of the articles.The result of the research shows that Implementation of Continous Audit will increase the accountability in state owned universities. Furthermore, the integrated information system is a major requirement of universities in financial governance